Application of the multivariate statistical analisis in investigation long-term durability of polymers. 1. The theory. - A. A. Valishin; T. S. Stepanova (Тонкие химические технологии)
The multivariate regressive analysis is used for statistical processing of experimental data in long-term durability of polymers. The most important statistical models of temperature-temporary dependence of durability (model of Jurkov and model of Regel-Ratner) were formulated. Formulas for finding statistical estimations of regresses coefficients and of physical parameters of durability were received. The full statistical analysis of models was carried out. In theory the problem of distinction statistical model of Jurkov from model of Regel-Ratner was solved. Thus, the problem of displacement of pole in temperature-temporary dependence of durability was solved.